(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2014)
Dowry death is a big evil prevailing in our society and the incidences of dowry death are not showing signs of decreasing to the level of compliance. Though the criminals have become tricky in committing and hiding the crime, homicidal post-mortem burning holds a good rank in that list. Post-mortem burns are commonly produced to create confusion regarding the cause and manner of death after an obvious crime like strangulation/throttling. Due to post-mortem artefacts, such as reddening and blackening of soot particles on the body, the autopsy surgeons can be misled in determining the ante-mortem or post-mortem nature of the burn and, thus, the real cause of death. Nevertheless, careful external and internal examination of the dead body and confirmatory chemical or/and histological examination can reveal the truth. In a similar case, a dead body of a married female was brought to us for autopsy examination with an alleged history of death due to electrical burns, as per the narration of the in-laws of the deceased and the inquest report of the investigating officer. On examination, 100% superficial-to-deep burns were present on the body, but no characteristic features of electrical burn were seen. Those burns were showing post-mortem characteristics, with the controversial feature of reddening on the posterior parts of the body and the typical internal findings of throttling/strangulation in the neck region, though the external findings could not be seen due to extensive and deep burns over the face and anterior parts of the body. Difference between the electrical and thermal burns, artefacts due to reddening and blackening in the post-mortem burns, throttling/strangulation with homicidal post-mortem burn pattern and their medico-legal significance are discussed in detail in this paper.